Diplomatic negotiation for representative in conflict resolution - Noor Muhammad, Salmah Jan (Science and Engineering Research Support Society, 2020)
Diplomatic representative an important person role in ensuring the sustainability of the relationships between governments and their must be well-versed in the negotiation process as well as possessing the agreeable communicative delivery skill. If the representative fails in managing his country’s diplomatic affairs with other countries, this may erupt a provocation and thus leads to a war. In this regard, negotiation for a diplomatic representative seems to be required for the resolution to a conflict arose. Hence, the objective of this study will identify and analyze the diplomatic negotiation for the representative in conflict resolution, especially during Malay Kedah Sultanate Government through the Al-Tarikh Salasilah Negeri Kedah manuscript. In addition, this research method will use the library method and research data analysis. The findings showed that the Malay Kedah Sultanate Government managed to resolve her conflicts with neighboring governments with several of diplomatic negotiation through the representative. In view of this, it is expected that this study will benefit to the researchers of diplomatic negotiation and conflict resolution management practiced by the Malay sultanate.